Correlation between QRS Complex Changes and Cardiac Iron Overload in Beta Thalassemia Major Patients Using T2*MRI - Mohammad Amini; Navidreza Mashayekhi; Bahman Sadeghi; Aziz Eghbali; Yazdan Ghandi (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Cardiac magnetic resonance imaging (MRI) is a costly method to assess cardiac iron overload. The presence of fragmented QRS (fQRS) indicates changes due to iron overload in cardiac tissue. The aim of this study was to evaluate the correlation between fQRS and cardiac iron overload using cardiac MRI in patients with β-thalassemia major (β-TM). Materials and methods: This analytical cross-sectional study was conducted in 40 β-TM patients admitted to Arak Amir-Kabir Hospital, Iran 2018-2019. Cardiac T2* MRI was performed and values of less than 20 ms were considered as cardiac iron overload. The patients were divided into two groups (<20 and >20 ms). The presence of fQRS was assessed on 12-lead surface electrocardiogram (ECG) and compared between two groups. Results: There was a positive correlation between T2*MRI and serum ferritin (r= 0.041, P=0.657) and hemoglobin levels (r=0.057, P=0.540). The mean T2*MRI in patients with fQRS (18.43±7.24) was significantly lower than patients without fQRS (26.47±6.15) (P=0.001). We found a negative correlation between T2*MRI and fQRS (r= -0.048, P=0.001). Conclusion: The presence of fQRS on ECGs could be a good predictor of cardiac iron overload in β-TM patients. It is believed that fQRS can indicate this change in electrocardiography and shows the need for more accurate monitoring for cardiac overload and aggressive chelation therapy.